Malondialdehyde and Antioxidant Vitamins in Breast Cancer Iraqi Patients - Firas A. Hassan (Journal of Global Pharma Technology, 2016)
The present research was proceeded to explore the situation of plasma anti-oxidative vitamins (E andC) and lipid peroxidation on sixty no patronize breast cancer patients and 30 salutary women. Alteration in the standard for “total antioxidant capacity”, malondialdehyide (MDA), Nitreic oxide (NO) were temperate in specimen patients influenced through breast tumor. The effect detected that plasma vitamin E and vitamin E regulated for the aggregated of cholesterol and triglycerides diminished significantly in patients group (p 0.01). The grade of (MDA) increment significantly in patients as contract to the control. considerable variation were also spotted amidst patients together (non-metastatic and metastatic) breast cancer according respects specimen(NO) that were minimize in metastatic by contrast together non-metastatic breast tumor.Keywords: Vitamin C, Lipid peroxide, Total Antioxidant capacity, Nitric oxide.